Cost-effectiveness of depressive episode pharmacological treatment - Jakovljević Mihajlo B.; Tetsuji Yamada; Ching Chia Chen; Stevanović Dejan S.; Jovanović Mirjana R.; Nikić-Đuričić Katarina D.; Rančić Nemanja K.; Savić Dejana M.; Biorac Nenad M.; Mihajlović Goran S.; Janković Slobodan M. (Hospital Pharmacology, 2015)
Background and Objectives There is a paucity of published cost-effectiveness studies of alternative scenarios in depressive episode acute medical care in Eastern European populations. Methods Prospective cost-effectiveness analysis was conducted on 65 depressive patients in a large university clinic [May 2010-February 2012]. Patient visits to attending psychiatrists were scheduled at baseline, 3rd and 8th week. HDRS-17 was deployed to assess clinical efficiency and Q-LES-Q-SF scale for life quality assessment. Resource use and costs were evidenced from the Clinic's electronic registry of discharge invoices [national currency 1 €≈115.85 CSD]. Societal perspective and time horizon of 14 weeks were adopted. Results No statistically significant difference in HDRS scores before and after introducing treatment [χ2=4.339; r=0.362]. QALY value increased by the following: 11.77 of the SSRI, 8.93 of the SNRI, and 12.54 of the heterocyclic antidepressant group. Mean ICERs were: SSRI to SNRI [-44,148 CSD/QALY]; SNRI to Heterocyclics [-45,716 CSD/QALY]; Heterocyclics to SSRI [-51,501 CSD/QALY]. Therapeutic response in increment free days: 28.69 days gained SSRI, 21.78 days SNRI, 30.59 days in heterocyclics. Incremental cost per additional depression free day gained was for: SSRI 346.38 CSD per day, SNRI 327.74 CSD, and heterocyclics 201.54 CSD. Conclusions This trial evidence elucidates that the heterocyclic antidepressants provide highest 'value for money' in QALYs for the depressive episode treatment. According to Incremental cost-effectiveness ratio calculations, heterocyclic antidepressant proved superior to other two options. Cost-effectiveness evaluations have heavier impact to clinical decision making with regards to major depressive disorder treatment in the absence of clear clinical superiority of any major pharmacological protocol.